Usefulness of magnifying endoscopy for diagnosis of sessile serrated lesion with dysplasia or carcinoma: Large retrospective study - Murakami, Takashi; Kamba, Eiji; Tsugawa, Naoki; Fukushima, Hirofumi; Shibuya, Tomoyoshi; Yao, Takashi; Nagahara, Akihito (Endoscopy International Open, 2024)
Background and study aims Sessile serrated lesions (SSLs) are precursor lesions in the serrated neoplasia pathway that lead to invasive carcinoma from dysplasia arising from SSLs. This study aimed to elucidate the clinicopathological and endoscopic features of SSLs with and without dysplasia or carcinoma.Patients and methods We reviewed the clinicopathological and endoscopic data from all colorectal lesions pathologically diagnosed as SSLs at Juntendo University Hospital, Tokyo, Japan, between 2011 and 2022. In addition to conventional endoscopic findings, we retrospectively evaluated magnifying endoscopic findings with narrow-band imaging (NBI) or blue laser imaging (BLI) using the Japan NBI Expert Team system and analyzed pit patterns using magnified chromoendoscopic images.Results Of the 2,132 SSLs, 92.5%, 4.7%, 1.8%, and 0.9% had no dysplasia, low-grade dysplasia, high-grade dysplasia, and submucosal invasive carcinoma, respectively. Older age, the proximal colon, and larger lesions were more frequently associated with SSLs with dysplasia or carcinoma. However, 41.3% of the SSLs with dysplasia or carcinoma were ≤ 10 mm in size. Endoscopic findings, such as (semi)pedunculated morphology, double elevation, central depression, and reddishness, were frequently found in SSLs with dysplasia or carcinoma. Furthermore, magnifying endoscopy using NBI or BLI and magnifying chromoendoscopy showed high sensitivity, specificity, and accuracy for diagnosing dysplasia or carcinoma within SSLs.Conclusions SSLs with and without dysplasia or carcinoma exhibit distinct clinicopathological and endoscopic features. In an SSL series, conventional endoscopic characteristics in addition to use of magnifying endoscopy may be useful for accurately diagnosing advanced histology within an SSL.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Colorectal cancer; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...)